Van mosterdgas naar zwaveldioxide. Over de oorsprong van de eerste zwaveldioxidemonitor - Buijsman, Ed (Studium, 2015)
Recently, this magazine published an article on the significance of the first monitor for sulphur dioxide in air and its role in the awareness of air pollution in The Netherlands (Cf. Studium 7:2 (2014) 97–104). A rather unknown aspect is the origin of the monitor. Archival research showed that the automatic measuring device has its roots in war time scientific research in the United States aiming to develop a measurement method for mustard gas on the battle field.